2018
DOI: 10.1136/bmjqs-2018-007957
|View full text |Cite
|
Sign up to set email alerts
|

Minor flow disruptions, traffic-related factors and their effect on major flow disruptions in the operating room

Abstract: Room design and layout issues may create barriers to task performance, potentially contributing to the escalation of FDs in the OR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…For example, handing instruments with even minimal delay can disturb the smooth process [52]; a similar argument can be made for the precision of movements. Problems in tight cooperation can obstruct goals or interrupt the workflow, may elicit anger and tense behavior, and may lower performance [53]. In this sense, tensions may serve as an indicator of coordination problems [54].…”
Section: Discussionmentioning
confidence: 99%
“…For example, handing instruments with even minimal delay can disturb the smooth process [52]; a similar argument can be made for the precision of movements. Problems in tight cooperation can obstruct goals or interrupt the workflow, may elicit anger and tense behavior, and may lower performance [53]. In this sense, tensions may serve as an indicator of coordination problems [54].…”
Section: Discussionmentioning
confidence: 99%
“…Kondutivitas atau hantaran (119)(120)(121)(122)(123)(124)(125)(126)(127)(141)(142)(143)(144)(145)(146)(147)(148) merupakan pengukuran dasar untuk mempelajari gerakan ion (149)(150)(151)(152) , konduktivitas atau daya hantar listrik adalah kekuatan seberapa kuat larutan dapat menghantarkan listrik (188) . Hantaran merupakan kebalikan dari hambatan listrik (195) .…”
Section: Hantaranunclassified
“…The OR design and surgical department layout have an essential impact on the intraoperative processes, and therefore the overall efficiency of the surgical procedures. For example, recent studies showed the correlation between OR and equipment layout and surgical workflow disruptions [4,5].…”
Section: Introductionmentioning
confidence: 99%